¡Abajo el fascismo! Denuncia antidictatorial, solidaridad y apoyo del Partido Comunista Argentino con el exilio chileno (1973-1990) - Natalia Casola (Nuevo mundo - Mundos Nuevos, 2021)
This article takes a panoramic tour of the main actions of antidictatorial denunciation, solidarity and cooperation with the Chilean exile in Argentina by organizations linked to the Argentine Communist Party between 1973 and 1990. In the first part, the long cycle of Chilean exile in Argentina is synthetically periodized. In the second part, the characteristics of the reporting networks and support modalities are addressed, emphasizing the role of local communism.